2001
DOI: 10.1074/jbc.m010914200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Regulation by Galectin-12, a New Member of the Galectin Superfamily

Abstract: Galectins are a family of ␤-galactoside-binding animal lectins with conserved carbohydrate recognition domains (CRDs). Here we report the identification and characterization of a new galectin, galectin-12, which contains two domains that are homologous to the galectin CRD. The N-terminal domain contains all of the sequence elements predicted to form the two ␤-sheets found in other galectins, as well as conserved carbohydrate-interacting residues. The C-terminal domain shows considerable divergence from the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
132
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 127 publications
(138 citation statements)
references
References 67 publications
4
132
1
1
Order By: Relevance
“…The cells were subsequently cultured in medium with insulin only. Cell cycle distribution during adipocyte differentiation was determined by flow cytometry of propidium iodide-stained cells fixed with ethanol as described previously (31).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The cells were subsequently cultured in medium with insulin only. Cell cycle distribution during adipocyte differentiation was determined by flow cytometry of propidium iodide-stained cells fixed with ethanol as described previously (31).…”
Section: Methodsmentioning
confidence: 99%
“…We (31) and others (30) have previously cloned human galectin-12 cDNA and found that it encodes a galectin with two CRDs. The N-terminal CRD is highly homologous to those of other galectins, whereas the C-terminal CRD shows significant divergence from the consensus sequence (31).…”
mentioning
confidence: 99%
See 3 more Smart Citations